2002
DOI: 10.1017/s0022336000042001
|View full text |Cite
|
Sign up to set email alerts
|

Artinskian conodonts from the Dingjiazhai Formation of the Baoshan Block, west Yunnan, southwest China

Abstract: Permian conodonts were recovered for the first time from the Dingjiazhai Formation, a well-known diamictite-bearing stratigraphic unit in the Gondwana-derived Baoshan Block in West Yunnan, Southwest China. The conodont fauna occurs in limestone units within the upper part of the formation and consists of Sweetognathus bucaramangus (Rabe), S. whitei (Rhodes), Mesogondolella bisselli (Clark and Behnken), and an unidentified ramiform element. Based on the known stratigraphic distribution of 5. bucaramangus (Rabe)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Reimers (1991) assigned the fauna to the Bolorian (Kungurian). Ueno et al (2002) reinterpreted the (Youngouist, Hawley et Miller) by Reimers (1991, pl. 1, fig.…”
Section: Age Of the Rabeignathus Bucaramangus Faunamentioning
confidence: 96%
See 3 more Smart Citations
“…Reimers (1991) assigned the fauna to the Bolorian (Kungurian). Ueno et al (2002) reinterpreted the (Youngouist, Hawley et Miller) by Reimers (1991, pl. 1, fig.…”
Section: Age Of the Rabeignathus Bucaramangus Faunamentioning
confidence: 96%
“…14 lateral platforms. Ueno et al (2002) suggested that the number of accessory nodes is a variable morphological feature, and is, therefore, not a good criterion for species discrimination. We think that Ueno et al's opinion about the variance of accessory nodes is reasonable, and therefore classified our specimens with only one accessory node to Rabeignathus bucaramangus.…”
Section: Fauna Contents and Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the Baoshan and Tengchong blocks of the western part of West Yunnan show strong Gondwanan affinities in terms of both stratigraphy and fossil faunas and floras of Carboniferous-Permian time (Jin 1994;Wang et al 2001). These two blocks are considered to form the fragments in West Yunnan of the Cimmerian continent (Ueno 1999(Ueno , 2003, which was separated from Gondwanaland at around late Early Permian time (Ueno et al 2002). The Changning-Menglian Belt between the Cathaysia-related tectonic units and Gondwana-derived blocks represents, in a broad sense, the remnant of the closed main Paleo-Tethys in this area Wu et al 1995;Metcalfe 1999;Ueno 1999;Ueno et al 2003).…”
Section: Changning-menglian Belt and Mid-oceanic Carbonatesmentioning
confidence: 99%